Perceived success of a rural economic development initiative in South Africa - Cassim, Shehnaz (My University, 2011)
Poverty and poverty reduction has received much attention in research and social policy formulation (Hagenaars and De Vos, 1988; Carter and May, 1999; Klasen, 2008). The poor in South Africa are likely to be black, living in rural areas with findings indicating a sixty-three percent poverty rate in these communities (Woolard and Leibbrandt, 1999). NGOs are a visible and acknowledged stakeholder in the development arena (Edwards and Hulme, 1992; Tandon, 2000). The Buffelshoek Trust was set up with the sole purpose of creating a fund whereby the proceeds would be utilised to assist disadvantaged people in located in the rural Manyeleti communities in the Mpumalanga province, South Africa (Buffelshoek Trust, 2001). The purpose of this study was to identify the factors possibly leading to poverty in these communities. In addition, the study aimed to establish the level of success of the “Dust Dreams” initiatives undertaken by the Buffelshoek Trust in these communities from the perspectives of the donors, the NGO’s management team and the communities’ members themselves. Respondents from within the communities were classified into three groups – community leaders, Headmasters and teachers and the learners in order to enable a more detailed analysis. The most frequently identified factors that possibly led to poverty in these communities include the lack of employment opportunities, the lack of education facilities and facilities for skills development and the lack of access to healthcare. Findings suggest that the Trust is meeting its stated aim of “Empowerment through Education”. Furthermore, the initiatives are perceived to be promoting economic development in these communities by the majority of the respondents. The perceptions of the learners however, differ significantly. Recommendations include the provision of skills development training for adult members of these communities, assisting community members to lobby policymakers and initiate programmes to promote gender equality. The issue of HIV/ AIDS needs to be addressed. The need for better communication between NGOs, the beneficiaries and donors is also highlighted.
MBA - WBS
Keywords: Rural economic development; Economic development, South Africa